2006
DOI: 10.1007/s00428-005-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic nature of apocrine breast lesions

Abstract: Epithelial cells of fetal breast glandular structures, at the third trimester of pregnancy (28 weeks), produce GCDFP-15, in the absence of specific apocrine morphology. Apocrine epithelium of the breast may be a normal process of differentiation rather than a result of metaplasia, and it has been demonstrated that it is estrogen-receptor, progesterone-receptor and bcl-2 negative, but androgen-receptor (AR) positive. The significance of AR expression in apocrine epithelium is uncertain. Apocrine epithelium is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Pure apocrine carcinoma is uncommon and not included in the current study. Androgen receptor expression has been shown to be associated with apocrine carcinoma, which is often negative for ER and PR [33]. Leal et al [34] reported that the expression rates for AR, ER, PR, and HER-2 in 35 apocrine DCIS were 97.1%, 5.7%, 2.9%, and 47%, respectively, regardless of unclear grades.…”
Section: Discussionmentioning
confidence: 97%
“…Pure apocrine carcinoma is uncommon and not included in the current study. Androgen receptor expression has been shown to be associated with apocrine carcinoma, which is often negative for ER and PR [33]. Leal et al [34] reported that the expression rates for AR, ER, PR, and HER-2 in 35 apocrine DCIS were 97.1%, 5.7%, 2.9%, and 47%, respectively, regardless of unclear grades.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, its role in human seminal fluid has been fully established [27 -31]. PIP is present at high concentration in BCF [32,33] and considered as a secretory marker of apocrine differentiation in breast carcinoma [34,35]. A large number of studies have been documented in the favor of aberrantly high expression of PIP in breast cancer specimens both at gene and protein levels [3, 36 -39].…”
Section: Site Of Expressionmentioning
confidence: 99%
“…Elayat et al [35] analyzed cell turnover in apocrine metaplasia and apocrine adenosis, concluding that apoptosis is not prevalent in such lesions and hypothesizing that at least some of them could be more susceptible to oncogenic changes. GCDFP-15, a 15-kD product of the AR target gene prolactin-induced protein, is often used as specific marker for apocrine differentiation and have been found in breast cysts [36] and breast cyst fluid [6,36].…”
Section: Protein Markers Specific To Benign Apocrine Lesionsmentioning
confidence: 99%
“…However, apocrine metaplasia is observed in up to 85% of women without breast cancer and up to 95% of women with breast cancer, based on autopsy data [5]. Despite this high prevalence, the origin of apocrine differentiation in the breast remains controversial, and several theories have been proposed [6].…”
mentioning
confidence: 99%